2020
DOI: 10.1002/bes2.1631
|View full text |Cite
|
Sign up to set email alerts
|

Stable Coexistence of Equivalent Nutrient Competitors Through Niche Differentiation in the Light Spectrum

Abstract: Niche-based theories and the neutral theory of biodiversity differ in their predictions of how the species composition of natural communities will respond to changes in nutrient availability. This is an issue of major environmental relevance, as many ecosystems have experienced changes in nitrogen (N) and phosphorus (P) due to anthropogenic manipulation of nutrient loading. To understand how changes in N and P limitation may impact community structure, we conducted laboratory competition experiments using a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Why not? Previous competition studies showed that species with different photosynthetic pigments can coexist in white light (Stomp et al 2004, 2007, Burson et al 2019. One might therefore expect ample opportunities for species coexistence when cyanobacteria and green algae compete for different colors of light.…”
Section: Comparison Of Theoretical and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Why not? Previous competition studies showed that species with different photosynthetic pigments can coexist in white light (Stomp et al 2004, 2007, Burson et al 2019. One might therefore expect ample opportunities for species coexistence when cyanobacteria and green algae compete for different colors of light.…”
Section: Comparison Of Theoretical and Experimental Resultsmentioning
confidence: 99%
“…Therefore, the earlier competition models were extended by incorporation of the full spectrum of light (Stomp et al 2004(Stomp et al , 2007. These spectral models predict stable coexistence of species if they absorb different parts of the light spectrum, a theoretical prediction that has been verified by both laboratory competition experiments and field data (Stomp et al 2004, 2007, Burson et al 2019.…”
Section: Introductionmentioning
confidence: 99%